The expression of a plasmid-specified exported protein causes structural plasmid instability in Bacillus subtilis. - Cordes, C (1996)
The rolling-circle plasmid pGP1 was used to study the effects of the expression of a plasmid-specified exported protein on structural plasmid stability in Bacillus subtilis. pGP1 contains a fusion between the Bacillus licheniformis penP gene, encoding a C-terminally truncated penicillinase, and the Escherichia coli beta-galactosidase (lacZ) gene. Two processes affected the accumulation of pGP1 variants with deletions in the penP-lacZ region. First, divergent transcription from genes upstream of penP-lacZ increased pGP1 deletion frequencies up to about 10-fold. Second, the removal of the PenP signal peptide resulted in completely stable plasmids, indicating that the entry of the PenP fragment into the protein export pathway is an important factor in the instability of pGP1. On the basis of these results, we propose a model in which the temporary anchoring of the plasmid to the membrane through the cotranscriptional and cotranslational entry of PenP into the protein export pathway creates domains of local hypersupercoiling, which we assume to be targets for deletion formation.